Effect of Tillage and Nutrient Management on Growth, Yield, Harvest Index and Nutrient Use Efficiency of Wheat (Triticum aestivum L.) in Indo-gangetic Plains of India - Kumar, Amrendra; Singh Pal, Mahendra; Ramu, N.; Semwal, M. P. (International Journal of Bio-resource and Stress Management, 2016)
The present experiment was carried out during 2013–14 and 2014–15 at Norman E. Borlaug Crop Research Centre, Govind Ballabh Pant University of Agriculture and Technology, Pantnagar, Uttarakhand, India representing the Tarai belt of Uttarakhand. The experiment was laid out in a split plot design with 18 treatments with 06 tillage options i.e. FIRBS, conventional tillage (CT), sub soiling (SS), zero tillage (ZT), minimum tillage with two pass of rotavator (MT) and permanent raised bed system (PRBS) in main plot and 03 nutrient levels i.e. 50% of recommended dose of fertilizers (50% RDF), site specific nutrient management (SSNM) and 100% recommended dose of fertilizer (RDF) in sub plot with three replications. The tillage options and nutrients levels influenced significantly most of the growth and yield attributes. Based on pooled values PRBS the highest grain yield that was statistically equal to FIRBS and SS. In general wheat grain yield was almost equal at PRBS, FIRBS and SS that was 9.5 and 16% and 32.5% greater than CT, MT and ZT respectively. The harvest index was also recorded significantly highest under FIRBS followed by PRBS and Nutrient use efficiency was recorded highest under PRBS followed by SS and FIRBS, though remained non significant on pooled basis. Similarly RDF produced highest grain yield on pooled basis that was 11.7 and 48.6% higher than SSNM and 50% RDF, respectively but the harvest index was found significantly highest under at 50% RDF. The Nutrient use efficiency was recorded significantly highest under 50% during growth stages.